Scaling up effective treatment of hypertension—A pathfinder for universal health coverage. Issue 10 (23rd September 2019) - Frieden, Thomas R.; Varghese, Cherian V.; Kishore, Sandeep P.; Campbell, Norman R.C.; Moran, Andrew E.; Padwal, Raj; Jaffe, Marc G.
Abstract: High blood pressure is the world's leading cause of death, but despite treatment for hypertension being safe, effective, and low cost, most people with hypertension worldwide do not have it controlled. This article summarizes lessons learned in the first 2 years of the Resolve to Save Lives (RTSL) hypertension management program, operated in coordination with the World Health Organization (WHO) and other partners. Better diagnosis, treatment, and continuity of care are all needed to improve control rates, and five necessary components have been recommended by RTSL, WHO and other partners as being essential for a successful hypertension control program. Several hurdles to hypertension control have been identified, with most related to limitations in the health care system rather than to patient behavior. Treatment according to standardized protocols should be started as soon as hypertension is diagnosed, and medical practices and health systems must closely monitor patient progress and system performance. Improvement in hypertension management and control, along with elimination of artificial trans fat and reduction of dietary sodium consumption, will improve many aspects of primary care, contribute to goals for universal health coverage, and could save 100 million lives worldwide over the next 30 years.